An in vitro anti-inflammatory effect of Thai propolis in human dental pulp cells - Nutthapong KANTRONG; Jittranut KUMTAWEE; Teerasak DAMRONGRUNGRUANG; Subin PUASIRI; Anupong MAKEUDOM; Suttichai KRISANAPRAKORNKIT; Pattama CHAILERTVANITKUL (University of São Paulo, 2023)
Abstract Objective To explore the potential for development of Thai propolis extract as a pulp capping agent to suppress pulpal inflammation from dental pulp infections. This study aimed to examine the anti-inflammatory effect of the propolis extract on the arachidonic acid pathway, activated by interleukin (IL)-1β, in cultured human dental pulp cells. Methodology Dental pulp cells, isolated from three freshly extracted third molars, were first characterized for their mesenchymal origin and treated with 10 ng/ml of IL-1β in the presence or absence of non-toxic concentrations of the extract from 0.08 to 1.25 mg/ml, as determined by the PrestoBlue cytotoxic assay. Total RNA was harvested and analyzed for mRNA expressions of 5-lipoxygenase (5-LOX) and cyclooxygenase-2 (COX-2). Western blot hybridization was performed to investigate COX-2 protein expression. Culture supernatants were assayed for released prostaglandin E2 levels. Immunofluorescence was conducted to determine involvement of nuclear factor-kappaB (NF-kB) in the inhibitory effect of the extract. Results Stimulation of the pulp cells with IL-1β resulted in the activation of arachidonic acid metabolism via COX-2, but not 5-LOX. Incubation with various non-toxic concentrations of the propolis extract significantly inhibited upregulated COX-2 mRNA and protein expressions upon treatment with IL-1β (p<0.05), resulting in a significant decrease in elevated PGE2 levels (p<0.05). Nuclear translocation of the p50 and the p65 subunits of NF-kB upon treatment with IL-1β was also blocked by incubation with the extract. Conclusions Upregulated COX-2 expression and enhanced PGE2 synthesis upon treatment with IL-1β in human dental pulp cells were suppressed by incubation with non-toxic doses of Thai propolis extract via involvement of the NF-kB activation. This extract could be therapeutically used as a pulp capping material due to its anti-inflammatory properties.